Az 1956-os egyetemi emlékezet formálása a Műegyetemen - Batalka, Krisztina (Per Aspera ad Astra, 2017)
In 1992 a Foundation was established at the Technical University with the aim to preserve the memory of 1956 by explaining the role of the university’s citizens in the revolution and to assist with the institution’s traditional joint festivity organized by the government and the university, held on 22 October since the change of regime. The Foundation, whose archives and records are kept at the Budapest University of Technology and Economics Archives, was created by the “historic” university classes of 1956 and those former students of the Technical University who witnessed and participated in the events. One of the first results of their operation in the early 1990’s was the research and publication of previously unknown university documents from 1956, as well as recording the recollections of those academics and former students who experienced the historical events. However, the most interesting part of the Foundation’s work was establishing the “cult” of the Assembly Hall rally, which was continued for the next 25 years. With the help of relatively subjective records, the present study introduces this activity by recalling the steps of the remembrance-reconstruction of 1956. Fotó: Budapesti Műszaki és Gazdaságtudományi Egyetem Országos Műszaki Információs Központ és Könyvtár